REE-Bearing Minerals in Tin Waste Dumps of Singkep Island: Geochemical Identification and Recovery - Ronaldo Irzon (Geological Agency, 2022)
DOI:10.17014/ijog.9.1.15-26Instead of environmental hazard, tailing might contain resources which could be reworked with the development of mining and separation technologies. Tailing dumps and waste ponds which associated with the long period of tin mining are easily found in Singkep Island. The waste should be processed to recover and purify precious metals within, and to reduce environmental degradation. REE-bearing minerals identification in tin tailing based on trace and rare earth element abundances is the aim of this study. Concise mineral beneficiation is illustrated for any further re-work strategy. The tailings collected from four locations in Singkep were analyzed for their trace and rare earth element compositions using ICP-MS at The Centre for Geological Survey. REE content in concentrates was upgraded at the range of 9 to 94 folds of the corresponding wastes. Monazite-(Ce), xenotime, and zircon are the REE-bearing minerals of the studied samples according to the elemental composition. Gravity, flotation, magnetic, and electrostatic methods would be applicable to separate the REE-bearing minerals from the tailing.